From Husserl to Freire: reflections on the concept of competence on the National Common Curricular Base - Anderson Luiz Tedesco; Ivan Luís Schwengber (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2020)
This paper originates from a reflection on the term competence (and skill), concepts widely discussed in Brazilian education policies until the homologation and publication process, on December 14th, 2018, of the National Common Curricular Base (Base Nacional Comum Curricular - BNCC). The objective was to understand that, in the process of elaborating and implementing the BNCC, the concepts of competence and skill revealed a principle of awareness. Therefore, the research problem aimed to ponder about the definition of awareness that gave theoretical support to the elaboration of the BNCC. When assuming a qualitative approach, it was a study whose methodological procedures were based on bibliographic research. Based on the results, subsidies of different proposals of awareness in thinking were identified from Edmund Husserl to Paulo Freire, which could contribute to the epistemological bases of the BNCC. It is concluded that, when there is no deep and democratic discussion on education policies, the worst of humanity is preserved: conservatism and obscurantism expressed in the concept of awareness as competence in the BNCC.